2022
DOI: 10.31357/ait.v2i1.5444
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Extraction Techniques on Phytochemicals and Antioxidants Activity of Garcinia quaesita Leaves

Abstract: Garcinia quaesita is an endemic plant in Sri Lanka with a wide array of domestic and medicinal values, yet very limited studies have been reported. The goal of this study was to investigate the phytochemicals and antioxidants capacity of leaves of G. quaesita under different extraction techniques in order to monitor the effect of extraction techniques on the above parameters. Water was used as the solvent and four extraction methods, namely sonication (EN01, one-hour,RT, 40 kHz), Soxhlet (EN02, six-hours, 105 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 0 publications
0
14
0
1
Order By: Relevance
“…Finally, considering the LC 50 and LC 90 values, the extract of the G. zeylanica is the most appropriate for potential controlling programs of mosquito larvae. Kishore et al (2011) reviewed the efficacy of phytochemicals against mosquito larvae according to their chemical nature and have described the mosquito larvicidal potentiality of several plant derived secondary materials such as alkanes, alkenes, alkynes and simple aromatics, essential oils and fatty acids, lactones, terpenes alkaloids, steroids, isoflavonoids, pterocarpans and lignans (Son & Tram 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, considering the LC 50 and LC 90 values, the extract of the G. zeylanica is the most appropriate for potential controlling programs of mosquito larvae. Kishore et al (2011) reviewed the efficacy of phytochemicals against mosquito larvae according to their chemical nature and have described the mosquito larvicidal potentiality of several plant derived secondary materials such as alkanes, alkenes, alkynes and simple aromatics, essential oils and fatty acids, lactones, terpenes alkaloids, steroids, isoflavonoids, pterocarpans and lignans (Son & Tram 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It has Fruits with a diameter of up to 8 cm and a glossy pale-yellow color. G. zeylanica is used to treat Ulcers, Rheumatism, Bowel problems, Anorexia, Chronic dyspepsia, for fractures and it has medical properties like Antiseptic (Kokilananthan et al 2022). Garcinia is grown specifically to harvest its fruits, which are then used in food as a spice or condiment and in various forms of ayurvedic or traditional medicine (Kokilananthan et al 2022).…”
Section: Test Plant Materials Collection and Preparationmentioning
confidence: 99%
“…Trolox ((±)-6-hydroxy-2, 5, 7, 8-tetramethylchromane-2-carboxylic acid) was used as a standard, and the results were expressed in μL Trolox Eq/L. [ 11 12 ]…”
Section: Methodsmentioning
confidence: 99%
“…Kokilananthan et al previously published two articles based on chemical analysis of leaves, which revealed that the methanolic and aqueous extracts contain several important phytochemicals with antioxidative potential (AP), such as flavonoids, saponins, alkaloids, phenolics, and terpenoids. [ 7 8 ] As no previous studies on the essential oils (EOs) of these two plants' leaves, and currently EOs are attracted considerable interest from scientific community, this work aimed to extract the EOs from the leaves of G. zeylanica and G. quaesita and analyze the CCs and the AP of them.…”
Section: Introductionmentioning
confidence: 99%
“…Qualitative tests for bioactive compounds such as polyphenolic, tannin, flavonoid, saponin, alkaloid, terpenoid, coumarin, glycoside, anthocyanin, betacyanin, chalcones, and quinones of methanolic extract were carried out in triplicates using standard procedures described in the literature (Abubakar and Haque, 2020;Gayathri and Kiruba, 2014;Kokilananthan et al, 2022c;Wadood et al, 2013). Quantification of some phytochemicals 0.10 g of methanolic extract was dissolved in 0.25 ml of DMSO and diluted with 100.0 ml of methanol to make a 1000 ppm concentration.…”
Section: Chemical Analysis Of Phytochemicalsmentioning
confidence: 99%